Economic and environmental impacts of the coal-to-gas policy on households: Evidence from China. (20th March 2022) - Chen, Zhengjie; Tan, Yanyan; Xu, Juan
Abstract: As the world's largest carbon emitter, China faces serious air pollution problems. Given that both carbon dioxide and air pollutants mainly come from burning of fossil fuels, the coal-to-gas policy has received widespread attention as a way to steer the public towards cleaner energy. However, inflexibility in the early implementation of the coal-to-gas policy caused a shortage of natural gas, and thus had negatively influenced households' lives. Considering the importance of clarifying the economic and environmental impacts of the coal-to-gas policy, this paper employs a dynamic recursive computable general equilibrium (CGE) model and sets different substitution scenarios, to simulate the impacts of the coal-to-gas policy on gross domestic product (GDP), sectoral output, trade, carbon emission reduction, and air quality improvement. The simulation results show that the long-term damage to GDP will be weaker than the short-term one, and carbon emissions would be reduced by 280 and 300 million tons in 2030 under the high and full substitution scenarios, respectively. The emissions of air pollutants (SO2 and NOx ) would also decrease significantly. Moreover, our results indicate that it is feasible to increase the substitution ratio in a stepwise manner and eventually achieve full substitution, which can not only effectively avoid shortages of natural gas, but also promote the coordinated control of carbon dioxide and air pollution emissions. Highlights: Coal-to-gas policy is a more effective way to reduce CO2 emissions than SO2 and NOx emissions. The full alternative scenario with a step-by-step substitution approach should be adopted. Coal-to-gas policy will reduce GDP, and the long-term impact is weaker than the short-term impact. Some subsidies or tax incentives could be given to exports of resource-intensive goods.